Pendampingan Warga Binaan Rehabilitasi Narkoba Kota Banjar dalam Pemanfaatan Tanaman Lokal - Rohimah, Siti; Hertini, Reni; Suhariyanti, Enik; NIralam, Deni; Permana, Indra; Zulfikar, Zulfikar (Yayasan Inspirasi El Burhani, 2024)
This community service program aims to assist drug rehabilitation inmates in utilizing local plants such as Hangasa (Amomum dealbatum), Parahulu (Vatica scortechinii), and Honje (Toona sinensis) for health and environmental conservation. This program was conducted with a participatory approach for 1 week, involving 50 participants who received theoretical and practical training. Quantitative results showed a significant increase in participants' knowledge and skills, with an average increase of more than 28% in all aspects assessed. Qualitative results showed an increase in participants' awareness of the importance of environmental conservation and positive social impacts in the form of working group formation and community empowerment planning. In conclusion, this program was successful in increasing knowledge and skills in supporting environmental conservation. Recommendations for future implementation include developing sustainable support and increasing public education. This holistic approach has the potential to be applied in other locations to support community rehabilitation and development.